2015
DOI: 10.4103/0253-7613.165195
|View full text |Cite
|
Sign up to set email alerts
|

Trends in self-medication for dental conditions among patients attending oral health outreach programs in coastal Karnataka, India

Abstract: Objectives:To determine the prevalence, pattern, and awareness of self-medication practices among patients presenting at oral health outreach programs in coastal Karnataka, India.Materials and Methods:The cross-sectional study, based on an interview conducted in randomly selected 400 study subjects from the patients presenting at these oral health outreach programs. Data were collected regarding demographic information and the interview schedule consisting of 14 questions was administered.Results:Prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 14 publications
3
29
0
4
Order By: Relevance
“…The practice of self-medication for rapid relief of pain, fever or crying symptoms associated with toothache, can result in financial savings with consultations, examinations and treatments, and less time dedicated to child or adolescent care. It has been reported that in economically disadvantaged communities, where the level of schooling is lower, most episodes of pain are treated by self-medication [16,25]. Consistent with these reports, a study carried out with a low socioeconomic status population, residing in a rural area of India, showed that the most common form of self-care in cases of toothache was the use of over-the-counter medicines [22].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The practice of self-medication for rapid relief of pain, fever or crying symptoms associated with toothache, can result in financial savings with consultations, examinations and treatments, and less time dedicated to child or adolescent care. It has been reported that in economically disadvantaged communities, where the level of schooling is lower, most episodes of pain are treated by self-medication [16,25]. Consistent with these reports, a study carried out with a low socioeconomic status population, residing in a rural area of India, showed that the most common form of self-care in cases of toothache was the use of over-the-counter medicines [22].…”
Section: Discussionmentioning
confidence: 80%
“…In the context of oral health, one of the most common reasons for one's self-medication is toothache, which can have varying causes such as dental eruption and tooth decay. Since it is a process characterized by painful symptoms, analgesic and anti-inflammatory drugs are most commonly used by patients presenting with toothache, in order to avoid or postpone visits to the dentist [15,16]. In schoolchildren, parent/caregiver anxiety and fear of dental care may be the leading reasons for the practice of self-medication for toothache [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is the subjective nature of perceived dental care because they were influenced by an individual's viewpoint on the sense of his or her oral health and problem. [ 18 19 ] Therefore, it is not only the severity of signs and symptoms of dental illness which influence perceived need for care but it can also be influenced by dental health literacy. [ 20 21 ] Many people are often unaware of their dental care needs, which may be due to less severity of pain and unaffected daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…This findings was in agreement with many studies conducted by previous authors. [ 1 16 17 18 19 20 ] However, male preponderance was recorded in the studies carried out by other researchers. [ 21 22 23 ] It is generally believed that women are more health conscious and seek health services more frequently and better health practices than men.…”
Section: Discussionmentioning
confidence: 99%